Of Mice and Men Opera Still - Ron Scherl:::Creator::::::::::::
The Spring Opera Theater's production of Carlisle Floyd's operatic adaptationg of 'Of Micce and Men.' William Neill (Lennie) touches Alexandra Hunt's (Curley's wife's) hair.